Raising Expectations in Literacy for Students with Extensive Support Needs Using Multiliteracies - Krishnan, Sudha V. (Journal of the American Academy of Special Education Professionals, 2024)
Multiliteracies provide a unique opportunity to students with extensive support needs (ESN) because they extend literacy practices to include print-based texts along with the visual, audio, gestural, and spatial modes, thereby engaging students in literacy practices and higher-level skills regardless of their fluency in language or learning modality. However, many teachers of students with ESN are not familiar with multiliteracies or how to implement these in their classrooms. This paper provides a framework for implementing multiliteracies in the classroom using the four knowledge processes specified in the pedagogy: experiencing, conceptualizing, analyzing, and applying.